An impact of the ladle lining on the refining of reinforced steel when blowing with powders - Babanli, Mustafa; Karimov, Ramin; Bayramov, Aydin; Abbasov, Ibrahim Isa (Eastern-European Journal of Enterprise Technologies, 2019)
When refining steel by blowing powders, the ladle lining material plays a serious role. The dependency graphs of the degree of desulfurization on the consumption of silicocalcium powder during blowing in ladles lined with various materials have been presented. It has been noted that the amount of FeO in the slag seriously affects the average degree of desulfurization. With a large amount of FeO in the slag, the degree of resulfurization is greatly increased. The placement plan of the unit for refining the liquid steel in the ladle has been illustrated. Simultaneously, for powder blowing, a device diagram of the ladle furnace fitted with equipment for blowing liquid steel with powders has been presented. In this equipment, powder lining can be used and steel blowing with silicocalcium based powders can be carried out. The degree of desulfurization is also seriously affected by the initial amount of sulfur in the metal charge for steelmaking The presence of a roof in the pouring ladles improves the conditions for metal blowing, oxidation and metal loss are reduced. It has been observed that the process of refining liquid steel in a ladle is complex and depends on many factors. The amount of sulfur in the primary metal charge, the lining of the ladle, the composition of the powder of the blown material and the technological parameters of the blowing are important. The complete desulfurization of steel by blowing with powders primarily depends on the initial amount of sulfur in the metal. It has been found that there is a linear dependence of the final sulfur content on its initial content in steel when metal is blown in a ladle with a mixture of 70 % MgO, 20 % CaO, and 10 % CaF2. The desulfurization of steel by blowing with powders, especially by blowing magnesium and calcium alloys, can be significantly affected by ladle lining